Efficacy of High-Dose Synbiotic Additives for Deoxynivalenol Detoxification: Effects on Blood Biochemistry, Histology, and Intestinal Microbiome in Weaned Piglets - Jin-Young Jeong; Junsik Kim; Minji Kim; Sungkwon Park (Biology)
Deoxynivalenol (DON) is a common mycotoxin observed in cereal grains, and feed contamination poses health risks to pigs. Biological antidotes, such as synbiotics (SYNs), have garnered attention for mitigating DON toxicity. This study aimed to assess the efficacy of SYNs by comparing the blood biochemistry, histology, and gut microbiome of weaned piglets. A 4-week trial was conducted on 32 weaned piglets. After a week of diet and environmental adaptation, the pigs were divided into four groups: (1) control (CON, n = 8); (2) SYN (n = 8); (3) DON (n = 8); and (4) DON+SYN (n = 8). The SYN supplementation of weaned piglets increased the final body weight (21.71 ± 0.93 vs. 20.73 ± 0.84), average daily gain (0.38 ± 0.02 vs. 0.34 ± 0.02), and gain-to-feed ratio (0.49 ± 0.04 vs. 0.43 ± 0.02), and decreased the feed conversion ratio (2.14 ± 0.14 vs. 2.39 ± 0.13) compared to the DON group. A high dose of DON induced liver and colon fibrosis and liver and cecum apoptosis, which were alleviated by SYNs. Glucose in the DON group (84.9 ± 3.7) was significantly lower than in the control (101.3 ± 4.2). Additionally, both the DON and DON+SYN groups exhibited higher creatine (0.9 ± 0.0 and 0.9 ± 0.1) and lower cholesterol (88.3 ± 3.2 and 90.0 ± 4.8) levels (p < 0.05). In conclusion, SYNs alleviated DON toxicity, indicating its potential as an antidote for specific biomarkers.